Food Policy Councils, Lessons on inclusiveness - Halliday, J.C.T.; Veenhuizen, D.M.R. van (RUAF Foundation, 2019)
UA Magazine 36: Food Policy Councils. Urban Agriculture Magazine (UA Magazine) is produced by the RUAF. Global Partnership on Sustainable Urban Agriculture and Food Systems, in close collaboration with strategic partners on particular topics addressed in each magazine. UA Magazine facilitates the sharing of information on urban agriculture and urban food systems, promotes analysis and debate on critical issues for development of the sector, and publishes “good practices” and impact stories.